2014
DOI: 10.1007/s00701-014-2099-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of the bovine pericardial patch and fibrin sealant in meningomyelocele closure

Abstract: The usage of the bovine pericardial patch and fibrin sealant technique at the fascial level-between the dural sac and the skin-provides adequate soft tissue coverage in meningomyelocele repair surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Autologous and heterologous pericardium has been used in human medicine for a number of different applications, including cardiovascular procedures, [14][15][16] abdominal herniorrhaphy, 17 cholangioplasty, 18 meningomyelocoele closure, 19 treatment for corneal perforation 20 or tracheal reconstruction. 21 In veterinary medicine, pericardium has previously been used in cardiovascular surgery, [22][23][24][25][26] oesophageal patching, diaphragmatic herniorrhaphy 27 and closure of large defects.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous and heterologous pericardium has been used in human medicine for a number of different applications, including cardiovascular procedures, [14][15][16] abdominal herniorrhaphy, 17 cholangioplasty, 18 meningomyelocoele closure, 19 treatment for corneal perforation 20 or tracheal reconstruction. 21 In veterinary medicine, pericardium has previously been used in cardiovascular surgery, [22][23][24][25][26] oesophageal patching, diaphragmatic herniorrhaphy 27 and closure of large defects.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that, for instance, in meningomyelocele repair, which is the most common and complex birth defect of the central nervous system, consecutive separate closures of the neural placode, dura mater, lumbar fascia, subcutaneous layer, and skin need to be conducted. The use of a fibrin-enriched bovine pericardial patch at the fascial level—between the dural sac and the skin—provided sufficient soft tissue coverage in meningomyelocele repair surgery [ 122 ].…”
Section: Fibrin and Skin Reconstructionmentioning
confidence: 99%